Design and fabrication of a single cylinder diesel engine test platform and it's experimental equipment - Auji, Samsudin (2012)
This project focuses on the design and fabrication the main structure for diesel engine testing platform. It is a part of an engine performance testing of a single cylinder diesel engine. Diesel engine performance testing for the study of future biodiesel fuel would require a stand for engine mounting. To achieve the objective, the testing platform must be designed and analyzed the designed platform and its coupling plate. The Computer Aided Design (CAD) is use to design the platform using the dimension that have been measured earlier. For the analysis of the design, the SolidWork software is used to analyze it. The proposed design is prove to be reliable based on the analysis result. Finally, the engine platform for diesel engine testing has been developed.